Automatic measurement of head-perineum distance during intrapartum ultrasound: description of the technique and preliminary results. (18th July 2022) - Angeli, Laura; Conversano, Francesco; Dall'Asta, Andrea; Eggebø, Torbjørn; Volpe, Nicola; Marta, Simone; Pisani, Paola; Casciaro, Sergio; Di Paola, Marco; Frusca, Tiziana; Ghi, Tullio
Abstract: Objectives: To evaluate the accuracy and reliability of a new ultrasound technique for the automatic assessment of the head-perineum distance (HPD) during childbirth. Methods: HPD was measured on a total of 40 acquisition sessions in 30 laboring women both automatically by an innovative algorithm and manually by trained sonographers, assumed as gold standard. Results: A significant correlation was found between manual and automatic measurements (Intra-CC = 0.994). High values of the coefficient of determination ( r 2 =0.98) and low residual errors: RMSE = 2.01 mm (4.9%) were found. Conclusion: The automatic algorithm for the assessment of the HPD represents a reliable technique.